Control y regulación del derecho a la movilidad humana en el ámbito laboral privado para establecer un límite a la contratación de trabajadores extranjeros y garantizar el trabajo digno y estable para el trabajador nacional - Flores Armijos, Alan Enrique (2022)
This thesis deals with the title: Control and Regulation of the Right to Human Mobility in the Private Labor Sphere to establish a Limit to the Hiring of Foreign Workers and Guarantee Decent and Stable Work for the National Worker", evidence through the conceptual, legal and doctrinal review of the present topic, where it details the lack of a legal regulation and a legal vacuum existing in the Labor Code regarding the excessive hiring of foreign workers within the private sector, since in said norm the labor rights of all persons are guaranteed, Moreover, it does not emphasize that a limitation should be typified for employers in the private sector when hiring foreign workers, because it is evident that in recent years with the massive arrival of citizens from different countries to our territory has caused an imbalance in society, increasing the unemployment rate in the country and also caused labor instability for national workers, because there is no regulation that regulates and controls such hires, For this reason, the present investigation is aimed at the protection of dignified and stable work for Ecuadorians, thus, we also proceeded to analyze similar legal figures contained in comparative law regulations of countries such as Peru, Colombia, Guatemala and Mexico, which helped to understand the need to typify this limitation and in which several rules are established that should be collected by the Ecuadorian legal system, so that with its correct incorporation and application, the Ecuadorian legal system is respected, The Ecuadorian Labor Code is not clear and does not address the excessive hiring of foreign workers, causing employers in the private sector to take advantage of the foreign status of some workers and violate the rights of both nationals and foreigners. In order to reinforce the aforementioned criteria regarding the need to typify certain legal rules that are responsible for controlling, regulating, sanctioning and limiting the labor rights of national workers.